Clinical Scoring for Diagnosis of Acute Lower Abdominal Pain in Female of Reproductive Age - Jearwattanakanok, Kijja; Yamada, Sirikan; Suntornlimsiri, Watcharin; Smuthtai, Waratsuda; Patumanond, Jayanton (Emergency Medicine International, 2013)
Background. Obstetrics and gynecological conditions (OB-GYNc) are difficult to be differentiated from appendicitis in young adult females presenting with acute lower abdominal pain. Timely and correct diagnosis is clinically challenging. Method. A retrospective data analysis was performed on 542 female patients who were admitted to a tertiary care hospital with a chief complaint of acute lower abdominal pain. Diagnostic indicators of appendicitis and OB-GYNc were identified by stepwise multivariable polytomous logistic regression. Diagnostic performances of the scores were tested. Result. The developed clinical score is comprised of (1) guarding or rebound tenderness, (2) pregnancy, (3) sites of abdominal tenderness, (4) leukocytosis, (5) peripheral neutrophils ≥75%, and (6) presence of diarrhea. For diagnosis of appendicitis, the area under the ROC curve was 0.8696, and the sensitivity and specificity were 89.25% and 70.00%. For OB-GYNc, the corresponding values were 0.8450, 66.67%, and 94.85%, respectively. Conclusion. The clinical scoring system can differentiate the diagnosis of acute lower abdominal pain in young adult females. Time spent for diagnosis at the emergency room may be shortened, and the patients would be admitted to the appropriate departments in less time.